Conversational Implicature In Tampan Market Transactions: A Pragmatic Perspective For Language Learning - Sari, Lusi Komala; Putri , Desvia Mulya; Apakama, Lusi Mgbemgasha (Actual Insight, 2025)
This study aims to examine the violations and adherence to conversational maxims in verbal transactions between sellers and buyers at traditional markets in the Tampan District, Pekanbaru, using a pragmatic approach based on Grice’s theory of maxims. Through a descriptive qualitative method, data were collected via participant observation and direct recordings of natural conversations, which were then analyzed using contextual discourse analysis techniques. The findings reveal that violations of the maxims of quantity, quality, relevance, and manner are often carried out intentionally to generate conversational implicatures that are persuasive, polite, and adaptive to social norms. Sellers use maxim violations to persuade, guide consumer choices, or enhance the symbolic value of their products, while buyers employ them to negotiate subtly, maintain politeness, or foster social closeness. These findings indicate that both violations and adherence to maxims are not forms of pragmatic deviance, but rather represent complex and functional communication strategies. Interdisciplinary analysis reveals that this phenomenon is closely related to the concepts of politeness (Brown & Levinson), social impression management (Goffman), microeconomic negotiation, and reflections of local cultural values. Therefore, this study not only contributes to the field of pragmatic linguistics but also enriches understanding in intercultural communication, language education, and social anthropology. The implication is that integrating pragmatic awareness and real-life communicative strategies into classroom instruction can help students develop more adaptive, context-sensitive language skills for authentic social interaction.